Hypoxia Modulates the Phenotype of Osteoblasts Isolated From Knee Osteoarthritis Patients, Leading to Undermineralized Bone Nodule Formation. Issue 7 (July 2014) - Chang, Joan; Jackson, Sonya G.; Wardale, John; Jones, Simon W.
<x xml:space="preserve">Abstract</x> Objective To investigate the role of hypoxia in the pathology of osteoarthritic (OA) bone by exploring its effect on the phenotype of isolated primary osteoblasts from patients with knee OA. Methods OA bone samples were collected at the time of elective joint replacement surgery for knee or hip OA. Normal bone samples were collected postmortem from cadaver donors. Primary osteoblasts were isolated from knee OA bone chips and cultured under normoxic or hypoxic (2% O2) conditions. Alkaline phosphatase activity was quantified using an enzymatic assay, and osteopontin and prostaglandin E2 (PGE2) production was assayed by enzyme‐linked immunosorbent assay. Total RNA was extracted from bone and osteoblasts, and gene expression was profiled by quantitative reverse transcription–polymerase chain reaction. Results Human OA bone tissue sections stained positively for carbonic anhydrase IX, a biomarker of hypoxia, and exhibited differential expression of genes that mediate the vasculature and blood coagulation as compared to those found in normal bone. Culture of primary osteoblasts isolated from knee OA bone under hypoxic conditions profoundly affected the osteoblast phenotype, including the expression of genes that mediate bone matrix, bone remodeling, and bone vasculature. Hypoxia also increased the expression of cyclooxygenase 2 and the production of PGE2 by OA osteoblasts. Osteoblast expression of type II collagen α1 chain, angiopoietin‐like 4, and insulin‐like growth factor binding protein 1 was shown to be mediated by hypoxia‐inducible factor 1α. Chronic hypoxia reduced osteoblast‐ mineralized bone nodule formation. Conclusion These findings demonstrate that hypoxia can induce pathologic changes in osteoblast functionality consistent with an OA phenotype, providing evidence that hypoxia is a key driver of OA pathology.